Iconofagia e incomunicação: a violência na publicidade de alimentos animalizados, créditos bancários e agrotóxicos, dirigida a jovens e idosos - Lima, Aida Franco de (2014)
This research focuses on advertising related to animal origin food, credit cards/ consigned credit and the agrochemical sector, this last according to the so-called Agrinho program. Our purpose is to discuss how violence, consumerism and the lack of communication interconnect by means of themes exemplified from advertisements that have appeared in different periods and were displayed until 2014. Despite the apparent disparity from different contexts of production, our research selection has in common the presence of contents oriented to the consumption by children and an elderly public, even stimulating adhesion and sympathy in consumers. We worked from the hypothesis that media and advertising mechanisms adopted by the above-mentioned sectors accomplish a kind of "asepsis", that is, they detach the end products of their origins and processing. We argue that advertising in print newspapers, websites and television impacts the audience once they reveal the backstage of several advertising strategies. As main concepts we used non-communication , this one triggered by the excessive load of images conveyed by different media; "iconophagy", in which the images and bodies take turns in a devouring act in an environment encompassed by images; and "violence", this last allocated in seemingly innocuous contexts. Regarding our methodology, we studied comparatively concepts about the media universe, the images and the mechanisms of consumerism, confronting the selected ads when appropriated. As for our theoretical framework we had the support of Günter Anders, Norval Baitello Jr., Vilém Flusser, Malena Contrera Segura, Martin Lindstrom, Peter Singer, Sonia Terezinha Felipe, Carol J. Adams works, among others